Small RNA CjNC110 regulates the activated methyl cycle to enable optimal chicken colonization by Campylobacter jejuni - Brandon Ruddell; Alan Hassall; Orhan Sahin; Paul J. Plummer; Qijing Zhang; Amanda J. Kreuder (mSphere)
ABSTRACT Post-transcriptional gene regulation by non-coding small RNAs (sRNAs) is critical for colonization and survival of enteric pathogens, including the zoonotic pathogen Campylobacter jejuni. In this study, we utilized C. jejuni IA3902 (a representative isolate of the sheep abortion clone) and C. jejuni W7 (a highly motile variant of NCTC 11168, a human gastroenteritis strain) to further investigate regulation by sRNA CjNC110. Both motility and autoagglutination ability were confirmed to be phenotypes of conserved regulation by CjNC110. However, we demonstrated that W7∆CjNC110 does not change chicken colonization levels compared to W7 wild type, directly contrasting IA3902∆CjNC110, which had decreased colonization ability. Subsequently, we determined strain-specific phenotype variation between W7∆CjNC110 and IA3902∆CjNC110 when examining intracellular L-methionine (L-met) levels controlled by the activated methyl cycle (AMC). We hypothesized that the presence of a secondary system for L-met production conferred by MetAB in W7 but not IA3902 might explain the difference in both chicken colonization and L-met availability. Insertion of metAB within IA3902∆CjNC110 (naturally absent) restored intracellular L-met levels in IA3902∆CjNC110::metAB and overcame the colonization defect that resulted from mutagenesis of CjNC110 in IA3902. Deletion of metAB in W7∆CjNC110 (naturally present) led to a decrease in L-met in W7∆CjNC110∆metAB and a colonization defect which was otherwise masked in W7∆CjNC110. Our results indicate that regulation of the AMC leading to altered L-met availability is a conserved regulatory function of CjNC110 in C. jejuni and confirm that L-met generation via the AMC as activated by CjNC110 is critical for optimal host colonization.IMPORTANCEDuring this study, the regulatory action and conservation of function of CjNC110 between two different zoonotically important Campylobacter jejuni strains were examined. Critically, this work for the first time reveals regulation of L-methionine (L-met) production within the activated methyl cycle (AMC) by small RNA (sRNA) CjNC110 as a key factor driving C. jejuni optimal chicken colonization. As a growing body of evidence suggests that maintenance of L-met homeostasis appears to be critical for C. jejuni colonization, interventions targeting the AMC could provide a critical control point for therapeutic drug options to combat this zoonotic pathogen. Our results also indicate that even for conserved sRNAs such as CjNC110, strain-specific differences in phenotypes regulated by sRNAs may exist, independent of conserved regulatory action. Depending on the strain examined and accessory genomic content present, conserved regulatory actions might be masked, thus investigation in multiple strains may be warranted.